Ductilization of high carbon, high silicon carbide-free nanostructured bainitic steel - Gupta S.K.; Manna R.; Chattopadhyay K. (My University, 2025)
In the present study, the influence of the volume fraction of blocky austenite on the microstructure and mechanical properties of novel bainitic steel was investigated. The rolled homogenized sheets were austenitized at 950 °C and austempered at 250 °C for 18h (B15VA-1) and 50 h(B15VA-2). X-ray diffraction study of B15VA-1 & B15VA-2 confirmed the presence of carbide-free nanostructured bainitic ferrite (BF) and retained austenite (RA). Optical, scanning and transmission electron microscopic studies delineate the morphology of retained austenite to filmy and blocky forms. On the tensile deformation, majority of blocky austenite in B15VA-1 transformed to strain-induced martensite of ε type. Hardness and yield strength (YS) were increased with an increasing amount of bainitic ferrite, however, ultimate tensile strength (UTS) was found to be a strong function of the extent of strain-induced martensitic (SIM) transformation. As a result of the high amount of SIM, UTS of B15VA-1 increased to 1889 MPa. Ductility is mainly controlled by the transformation-induced plasticity of blocky austenite. Uniform plastic elongation and total plastic elongation were found to be 25% and 28%, respectively. The work hardening behavior can be described by the Swift model. Deformation under tensile load takes place in three stages which are homogeneous deformation, strain-induced martensitic transformation and multiphase deformation-led interaction of dislocations and their recovery. The alloy with nanostructured bainitic ferrite fails by mixed mode of ductile-brittle fracture. © 2022